Sleep deprivation impairs synaptic tagging in mouse hippocampal slices - Vecsey, Christopher G. (Neurobiol Learn Mem, 2018)
Metaplasticity refers to the ability of experience to alter synaptic plasticity, or modulate the strength of neuronal connections. Sleep deprivation has been shown to have a negative impact on synaptic plasticity, but it is unknown whether sleep deprivation also influences processes of metaplasticity. Therefore, we tested whether 5 h of total sleep deprivation (SD) in mice would impair hippocampal synaptic tagging and capture (STC), a form of heterosynaptic metaplasticity in which combining strong stimulation in one synaptic input with weak stimulation at another input allows the weak input to induce long-lasting synaptic strengthening. STC in stratum radiatum of area CA1 occurred normally in control mice, but was impaired following SD. After SD, potentiation at the weakly stimulated synapses decayed back to baseline within 2 h. Thus, sleep deprivation disrupts a prominent form of metaplasticity in which two independent inputs interact to generate long-lasting LTP.